2015
DOI: 10.1007/s11051-015-3084-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigating factors influencing consumer willingness to buy GM food and nano-food

Abstract: Emerging technologies applied to food products often evoke controversy about their safety and whether to label foods resulting from their use. As such, it is important to understand the factors that influence consumer desires for labeling and their willingness-to-buy (WTB) these food products. Using data from a national survey with US consumers, this study employs structural equation modeling to explore relationships between potential influences such as trust in government to manage technologies, views on rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 51 publications
3
52
0
Order By: Relevance
“…They want labeling for all types of food and are also willing to pay for this, since they believe that labeling facilitates informed decisions related to risk management. Consumers also believe that they have a right to be informed (Brown and Kuzma 2013; Yue et al 2015).…”
Section: Method Research Questions and Analytical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…They want labeling for all types of food and are also willing to pay for this, since they believe that labeling facilitates informed decisions related to risk management. Consumers also believe that they have a right to be informed (Brown and Kuzma 2013; Yue et al 2015).…”
Section: Method Research Questions and Analytical Frameworkmentioning
confidence: 99%
“…(iii) Develop targeted audience-specific communication When considering solutions, the focus is on targeted communication based on an understanding that the public is fragmented and that different audiences respond to information in different ways. Targeted nanotechnology communication is tailored to the understandings, values, needs, and knowledge of particular groups, with the aim of helping them understand nanotechnology and gain the tools needed to make well-balanced decisions for themselves (Duncan 2011;Ho et al 2010Ho et al : 2710Pillai and Bezbaruah 2017: 41;Yue et al 2015). Targeted communication is understood by its advocates as helping empower the public by providing information, so that members of the public might become informed despite their knowledge limitations (Simons et al 2009(Simons et al : 1596.…”
Section: (Ii) Academic Research On Public Understandingmentioning
confidence: 99%
“…Research showed attitudes toward nanotechnology to be moderately positive across many areas of application. Benefits were expected to occur predominantly in relation to medicines and health, and technological development, rather than to agriculture and food (Boholm & Larsson, 2019;Capon et al, 2015;Conti, Satterfield, & Harthorn, 2011;Frewer, 2017;Frewer et al, 2014;Giles, Kuznesof, Clark, Hubbard, & Frewer, 2015;Priest, 2009;Siegrist et al, 2007;Yue, Zhao, Cummings, & Kuzma, 2015). Food-related applications were also more likely to raise societal concern than other applications, and the application of nanotechnology in food was perceived to be less beneficial than in food packaging (Capon et al, 2015;Siegrist et al, 2007;Siegrist et al, 2008).…”
Section: Nanotechnology: Acceptance and Decisionmakingmentioning
confidence: 99%
“…Factors that affect acceptance at the individual level include risk and benefit perceptions, emotions, the perceived ability to cope with the risk, trust in the food industry and confidence in the competence of governmental technology management (Capon et al, 2015;Frewer et al, 2014;Kuttschreuter, 2006;Martensen, Brockenhuus-Schack, & Zahid, 2018;Siegrist et al, 2007;Siegrist et al, 2008;Viscecchia, De Devitiis, Carlucci, Nardone, & Santeramo, 2018;Yue et al, 2015).…”
Section: Nanotechnology: Acceptance and Decisionmakingmentioning
confidence: 99%
See 1 more Smart Citation